Interaction of Natural and Cultural Elements of Village Names in Banyumas Regency: Study of Toponymy - Oktaviana, Ika; Junawaroh, Siti; Lapiana, Ummi Nurjamil Baiti (HUMANIKA, 2025)
This study delves into the complex relationship between natural and cultural elements in shaping the meanings of village names in Banyumas Regency. By using a qualitative approach that involves archival research and interviews with local residents, the research uncovers how these elements work together to maintain the region’s ecological and cultural identity. Through the analysis of the region's toponymy, the study identifies two main factors influencing village names: physical and non-physical nature. The physical nature includes geographical features such as hydrology, morphology, and biodiversity, while the non-physical nature encompasses intangible factors like climate and cultural heritage. The findings reveal that village names often mirror the local environment, historical events, and cultural stories, offering valuable insights into the community’s bond with their natural surroundings. This research adds to the understanding of how place names act as a repository of cultural and ecological knowledge, highlighting the significance of safeguarding the intangible heritage embedded within the toponymy of Banyumas Regency.